Tissue distribution of a novel aquaporin in a teleost fish (Sparus auratus) - Estêvão, Dulce (2003)
The aquaporin family consists of two principal groups of transmembrane proteins which function as channels for non-ionic compounds. The CHIP (CHannel forming Integral Protein) group functions only as water channels (aquaporins) and the GLP (GLycerol intrinsic Protein) group transports primarily glicerol but also water and other small solutes. A sea bream AQP-3 cDNA encoding a protein of 298 amino acids was isolated from a kidney cDNA library. The tissue distribution of this GLP family member was investigated by in situ hybridisation. Tissues, liver, gastrointestinal tract, kidney, head kidney, gonads and gills, were fixed in 4% PFA, dehydrated, embedded in wax and serial sections (8µm) mounted on poly-L-lysine coated slides. The AQP-3 probe was generated from the full length cDNA after digestion with BamHI followed by purification. In vitro transcription was carried out using T7 RNA Polymerase and Digoxigenin-RNA labeling mix to synthetize a specific riboprobe. Tissues were hybridised overnight at 54ºC followed by stringency washes in 2xSSC. Detection of hybridised probe was carried out using anti-digoxigenin-AP Fab fragments. The chromagens for colour detection were NBT (4-Nitroblue tetrazolium chloride) and BCIP (5-Bromo-4-Chloro 3-indolylphosphate). Sections were analysed using a microscope coupled to a digital image analysis systems. Results showed that the expression of AQP-3 was abundant in cells scattered in the lamina propria of the hindgut and in occasional cells localised at the interface of the circular and longitudinal muscle layer in the hindgut. Expression was also abundant in some tubules of the kidney and in putative chloride cells in the gills. Some cells stained intensely in the head kidney and in gonads signal was intense in the cytoplasm of larger oocytes, in the head of some sperm and in unidentified cells scattered in testicular tissue. The signal obtained in the mid gut and duodenum was much weaker and no signal was detected in the liver.